Prospecting and development of antimalarials from some medicinal plants - Chan, Kit Lam (Universiti Putra Malaysia, 2014)
The rapid emergence of multidrug resistant malarial parasites of Plasmodium falciparum, particularly against chloroquine, sulpha-pyrimethamine combinations, quinine and mefloquine has prompted a search for other chemotherapeutic agents of novel origin either from the plant kingdom or synthetic source. Amongst the medicinal plants, artemisinin, a sesquiterpene lactone with a bridged peroxide linkage, isolated from the Chinese herb, Artemisia annua L. (Asteraceae), and its derivatives are presently the only effective antimalarial drugs especially against cerebral malaria. From X-ray studies, a new triclinic artemisinin has been identified and shown to possess higher dissolution rate and bioavailability than the presently available orthorhombic crystal, suggesting that a lower dose of the triclinic polymorph may be used to achieve similar therapeutic activity as the presently available commercial product. Other plants from the Simaroubaceae family have been used as traditional medicines in China, Viet Nam, Myanmar, Indo-China and South-East Asia against various diseases including fevers and malaria. Eurycoma longifolia Jack, Bruceajavanica (L.) Merr. and Ailanthus altissima (Mill) Swingle are some examples investigated for their chemical constituents, antimalarial and toxicological properties. Several derivatives ofeurycomanone from E. longifolia were synthesized by direct and selective acylation of its 15-hydroxyl group. The former resulted in the yield of several 1,15-disubstituted derivatives [1,15-di-0-isovaleryleurycomanone, 1,15-di-0- (3,3-dimethylacryloyl)eurycomanone and 1,15-di-O-benzoyleurycomanone]. The latter method involved the initial protection of the hydroxyl groups of eurycomanone with trimethylsilyltrifluoromethane sulphonate. This was followed by selective desilylation to expose the targeted 15-hydroxyl group for subsequent acylation with the acid chloride to produce the monoacylated eurycomanone derivative. The antiplasmodial activities of the mono and diacylated derivatives against the chloroquine-resistant and sensitive P. falciparum parasites and their toxicities were discussed and compared with their parent compound.